Fractional order heroin epidemic dynamics - Zafar, Zain Ul Abadin; Rezazadeh, Hadi; İnç, Mustafa; Nisar, Kottakkaran Sooppy; Sulaiman, Tukur A.; Yusuf, Abdullahi (Elsevier, 2021)
Using illicit drugs has been on growth in all over the world especially in the USA, Europe and Asia. It is very harmful to society; it is the fourth foremost cause of death in the United States when taking overdose drug (about the same as motor vehicle crashes). A drug that has a significant detrimental effect on a population as a whole is heroin, above all illegal substances. This work discussesthenon-classical mathematical model of White and Comiskey, demonstrating heroin epidemics. We present the existence of stable equilibrium numerically & mathematically. We will apply two methods (i) Adams Bashforth PECE method and (ii) Grunwald-Letnikovmethod (GLM) and simulate the model using Matlab software package. (C) 2021 THE AUTHORS. Published by Elsevier BV on behalf of Faculty of Engineering, Alexandria University.
Keywords: Heroin epidemics; Adams Bashforth Moulton method; Grunwald-Letnikov method; White and Comiskey model; Stability analysis